Historia universal Siglo XXI. 1. Prehistoria / compilado por Marie-Henriette Alimen y P. Marie-Joseph Steve - Alimen, Marie-HenrietteSteve, P. Marie-Joseph (Historia universal Siglo XXI ; 1)
1a ed. (1970), 3a ed. (1972), 12a ed. (1978), 23a ed. (1989)